(untitled) (Baghdad Science Journal, 2006)
The study included a statement toxicity of some heavy metals individually and collectively and the existence of plant nutrients in the center Agirenk bluish green moss growth and Askhaddm biomass as an indicator of the study, in addition to portability moss on the accumulation of the metal